Модель прогнозування працездатності фундаменту парової турбіни - Красніков, Сергій Васильович (НТУ "ХПІ", 2014)
Розглядається оцінка вібраційного стану та прогнозування робочого стану фундаментів парових турбін за весь період експлуатації. На основі раніше розроблених методів проведено комплекс розрахункових та експериментальних досліджень фундаменту парової турбіни працючого енергоблоку електростанції. На основі отриманих даних проведено оцінку робочого стану в окремі періоди експлуатації, поточного робочого стану та остаточного стану. Побудовано криву стану конструкції. Отримано залишковий та загальний ресурс фундаменту. Зроблено рекомендації щодо подальшої експлуатації фундаменту парової турбіни.

Considered the estimation and prediction of vibration condition of the working condition of the foundations for the entire period of operation. The bases are considered only as supporting structures steam turbines. A range of theoretical and experimental studies. Studies conducted on the basis of previously developed мethodics. Object of research is the foundation of the steam turbine unit employed domestic power. Calculated study based on the finite element method. For experimental studies used diagnostic system. This diagnostic system specifically designed for dynamic measurements of vibration in a wide frequency range. Based on these data, the following: assessment of working conditions in the individual periods of operation, assessment of the current condition and forecasting the final state of the turbine foundation. Powered condition curve design. The resulting residual shared resource and the foundation of the steam turbine. Make recommendations for the future operation of the foundation. The results used in practice for a steam turbine unit of national power.
Model of capacity for work of steam turbine foundation
Keywords: енергоблок електростанції; період експлуатації; вібраційний стан; робочий стан; ресурс фундаменту; performance; vibration condition; vibration; foundation; steam turbine